Strategi Penerapan Sistem Manajemen Persediaan Untuk Meningkatkan Efisiensi Biaya Operasional Dengan Pendekatan Economic Order Quantity (EOQ) Pada UMKM Kuliner Dapoer Itha: Strategies for Implementing an Inventory Management System to Improve Operational Cost Efficiency Using the Economic Order Quantity (EOQ) Approach at Dapoer Itha, a Culinary SME - Tia Ananda Eka Sawitri; Zian Fachrian (OGZ Research & Publishing, 2026)
Food-related MSMEs face serious challenges in managing raw material inventory, which directly impacts the efficiency of their operating costs. Objective: This study aims to analyze the current state of the inventory management system, calculate the optimal Economic Order Quantity (EOQ), safety stock, and reorder point, and formulate an EOQ-based implementation strategy for the food-related MSME Dapoer Itha. Methods: This study employs a descriptive quantitative approach to determine the economic order quantity, safety stock, and reorder point, which requires measurable numerical calculations that can be mathematically verified using the EOQ formula. Research Results: The research findings indicate that Dapoer Itha’s inventory system remains conventional and reactive, relying entirely on the owner’s memory without structured inventory records, which leads to recurring stockouts during periods of high demand and overstocking that increases storage costs. The application of the EOQ method to key raw materials such as eggs, sugar, wheat flour, butter, and chocolate proved capable of optimizing the economic order quantity, establishing adequate safety stock, and determining the appropriate reorder point to prevent production disruptions. EOQ implementation is recommended through three phased stages: establishing an inventory tracking system, implementation accompanied by periodic evaluations. This study contributes to the EOQ literature for micro-scale culinary and bakery SMEs in rural areas while providing practical guidance for Dapoer Itha to improve cost efficiency and strengthen the business’s managerial foundation in a sustainable manner.